Pengaruh Indeks Pertumbuhan Manusia dan Pengangguran Terhadap Pertumbuhan Ekonomi : Penelitian - Tri Febriani Sipayung; Cheresentia Situmorang; Trivena Kezia Silaban; Hesti Herawati Siagian; Era Sulastri Hutasoit; Marshanda Siburian; Ria Agustina Sigiro (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the impact of the Human Development Index (HDI) and unemployment rate on economic growth in North Sumatera and the broader Sumatera Island region during 2019–2024 using panel data. Regression analysis with EViews 12 was conducted, testing Common Effect, Fixed Effect, and Random Effect models. The best model was selected based on Chow, Hausman, and Lagrange Multiplier tests, followed by classical assumption checks. Results indicate that HDI does not significantly influence economic growth due to time lags, mismatch between graduate skills and market needs, low quality of education and health, and dominance of traditional sectors. Conversely, the unemployment rate has a significant negative effect, with a 1% increase in unemployment causing a 2.33% decrease in economic growth. Simultaneous tests confirm that HDI and unemployment together significantly affect growth, explaining 36% of its variation, while other factors like investment and inflation account for the remainder. The study recommends integrated development policies focusing on improving human resource quality and reducing unemployment to support more inclusive economic growth in Sumatera.